Absence of low energy magnetic spin-fluctuations in isovalently and aliovalently doped LaCo2B2 superconducting compounds. (29th June 2016) - Majumder, M; Ghoshray, A; Khuntia, P; Mazumdar, C; Poddar, A; Baenitz, M; Ghoshray, K
Abstract: Magnetization, resistivity and 11 B, 59 Co NMR measurements have been performed on the Pauli paramagnet L a C o 2 B 2, and the superconductors L a 0.9 Y 0.1 C o 2 B 2 ( T c ≈ 4.2 K) and L a ( C o 0.7 F e 0.3 ) 2 B 2 ( T c ≈ 5.8 K). The site selective NMR experiment reveals the multiband nature of the Fermi surface in these systems. The temperature independent Knight shift and 1/ T 1 T clearly indicate the absence of correlated low energy magnetic spin-fluctuations in the normal state, which is in contrast to other Fe-based pnictides. The density of states (DOS) of Co 3 d electrons has been enhanced in superconducting L a 0.9 Y 0.1 C o 2 B 2 and L a ( C o 0.7 F e 0.3 ) 2 B 2 with respect to the non superconducting reference compound L a C o 2 B 2 . The occurrence of superconductivity is related to the DOS enhancement.